Effect of blue light intensity and photoperiods on the growth of diatom Thalassiosira pseudonana - Karthick Murugan, Palanisamy; Mohd Hasbi, Ab. Rahim; Natanamurugaraj, Govindan; Rameshprabu, Ramaraj; Palaniselvam, Kuppusamy; Gaanty Pragas, Maniam (Elsevier, 2022)
Diatom Thalassiosira pseudonana photosynthetic properties and generation of fucoxanthin and lipid production under different blue light intensity with different photoperiods (dark/light cycle) at temperature 23 ± 1 ◦C were studied in this work. The growth (cell number) and the biomass concentration of the cells were found to be doubled at 120 μE m− 2 s − 1 blue light intensity as compared to 200 μE m− 2 s − 1 at 8:16 h dark light photoperiods. The rise in blue intensity from 40 to 120 μE m− 2 s − 1 has increased the synthesis of fucoxanthin and lipid in Thalassiosira pseudonana at dark-light cycle 8:16 h. It was found that at optimal amount of blue light and photoperiod ratio, evidently influence the growth of Thalassiosira pseudonana by yielding 35.6 % lipid and 1.18 mg/g fucoxanthin.